Neo-Nazi terrorism and countercultural fascism the origins and afterlife of James Mason's siege - Sunshine, Spencer (Routledge studies in fascism and the far right, 2024)
"A new wave of aspiring neo-Nazi terrorists has arisen-including the infamous Atomwaffen Division. And they have a bible: James Mason's Siege, which praises terrorism, serial killers, and Charles Manson. Neo-Nazi Terrorism and Countercultural Fascism, based on years of archival work and interviews, documents for the first time the origins of Siege. First, it shows how Mason's vision arose from debates by 1970s neo-Nazis who splintered off the American Nazi Party/NSWPP and spun off a terrorist faction. Second, it unveils how four 1980s countercultural figures-musicians Boyd Rice and Michael Moynihan, Feral House publisher Adam Parfrey, and Satanist Nikolas Schreck-discovered, promoted, and published Mason. Neo-Nazi Terrorism and Countercultural Fascism explores a previously overlooked period and unearths the hidden connections between a countercultural clique and violent neo-Nazis-which together have set the template for today's Neo-Nazi terrorist underground. It is obligatory reading for those interested in contemporary terrorism, postwar countercultures, and the history of the U.S. Far Right and neo-Nazism